Designing a Web Based Application to Memorize Korean Vocabulary Using Flashcards - Intan Kumalasari (Riau Jurnal Teknik Informatika, 2025)
Korean language learning in the digital age is increasingly important as the global community's interest in Korean culture increases. One of the main challenges in learning Korean is memorizing vocabulary that is very large and has varying levels of difficulty. Traditional methods that are often used, such as manual memorization, are often less effective and tedious, thus lowering learning motivation. The main problem in learning Korean vocabulary is the lack of tools that can support the memorization process effectively and interactively. Many of the traditional methods used, such as jotting down vocabulary in books or manually repeating words, have proven to be less effective because they tend to be monotonous and do not provide direct feedback to the user. Additionally, the method is often poorly structured, making it difficult for users to monitor their progress or identify the vocabulary that needs more attention. The lack of interactive tools also has an impact on learning motivation, where users can quickly get bored or frustrated with slow progress. Therefore, this study aims to develop a web-based application that uses the flashcard method. The development method used is the Waterfall method, which consists of five main stages: needs analysis, system design, implementation, testing, and maintenance. At the needs analysis stage, user needs are identified to ensure that the application can meet their expectations. System design involves creating an optimal interface design, process flow, and database structure. The result of this research is a web-based application that allows users to memorize Korean vocabulary more effectively using the flashcard method. This application is equipped with an evaluation feature that helps users monitor their learning progress.